The Roman Republican castellum of Puig Castellar (Biosca): the earliest evidence for military headquarters in Hispania Citerior (180–120 BCE). Issue 2 (December 2022) - Rodrigo, Esther; Romaní, Núria; Carreras, Cesar; Pera, Joaquim; Catarineu, Laia
Abstract: This paper illustrates the results of research carried out at the archaeological site of Puig Castellar de Biosca (Catalonia, Spain), located in the northeast of the Iberian Peninsula. This Republican military fortress, a castellum, is exceptional due both to its early chronology, which ranges between 180 and 120 BCE, and to the fact that it acted as a long-lasting military installation situated in a pacified area on the periphery of the Celtiberian conflict zone. Work at the site has uncovered a central building on the top of a hill, which due to its Italian features has been identified as the headquarters of the military fortress. If this interpretation is correct, this might be one of the first examples of a Republican military headquarters building documented to date. It could then be considered a predecessor of later praetoria and principia, which have been recorded in the Numantine camps and on the Roman western limes .